Cryocoolers 11 2002
DOI: 10.1007/0-306-47112-4_55
|View full text |Cite
|
Sign up to set email alerts
|

Ductile, High Heat Capacity, Magnetic Regenerator Alloys for the 10 to 80 K Temperature Range

Abstract: New erbium-based regenerator materials have been developed as a replacement for lead in low temperature cryocoolers. These alloys have volumetric heat capacities which are 20 to 185% larger than that of lead from 10 to 80 K. These magnetic, ductile, oxidation resistant erbium alloys are more than 10 times stronger than lead and have a thermal conductivity ~10 times lower than lead. The alloys can easily be fabricated into spheres, foils, ribbons, and wires, and are environmentally friendly, non-toxic materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(106 citation statements)
references
References 4 publications
2
103
0
1
Order By: Relevance
“…Recently, we have shown that the magnetothermal properties for Er metal as a replacement for Pb as a 10 to 50 K regenerator material was significantly enhanced by alloying with Pr metal. 5,6 This has also been done for several binary intermetallic compounds 3 …”
Section: Improving Regenerator Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have shown that the magnetothermal properties for Er metal as a replacement for Pb as a 10 to 50 K regenerator material was significantly enhanced by alloying with Pr metal. 5,6 This has also been done for several binary intermetallic compounds 3 …”
Section: Improving Regenerator Propertiesmentioning
confidence: 99%
“…1,2 This modification enabled Toshiba scientists to lower the low temperature limit of the G-M cryocooler from ~10 K to ~4 K. Subsequently, several other lanthanide materials, in particular Nd 3 and HoCu 2 (Ref. 4), have been utilized for cooling down to ~4 K. More recently Er and Er-Pr alloys (up to 50 at.% Pr) have been suggested as a replacement for Pb 5,6 as the intermediate temperature (~10 to ~60 K) range regenerator material. Today research is still being continued on finding improved regenerator materials, especially below 10 K, in order to enhance the performance of Stirling, G-M, and pulse tube cryocoolers.…”
Section: Introductionmentioning
confidence: 99%
“…Heat capacity measurements revealed the 27 at.% Pr-Er alloy would be an excellent replacement for Pb for cooling down to -10 K. But if it were combined with a 50 at.% Pr-Er alloy in a compound low temperature stage regenerator (where the 50:50 alloy is at the cold end and the 27~73 alloy at the hot end) the efficiency and the cooling power would be increased even more [25] …”
Section: Cryocooler Regenerator Materialsmentioning
confidence: 99%
“…But since a low purity commercial grade of Er (96.8 at.% pure) was used in the development of the cryocooler materials [25], the high level of 0, N and C impurities (2.7, 0.3 and 0.2 at.%, respectively) in the Er may have had a significant influence on the observed magnetic behaviors. Thus, in order to determine the effect of Pr on the magnetic Er structures, high purity Er and Pr prepared at the Ames Laboratory (both 99.8 at,% pure) were used in this study.…”
Section: The Er-rich Er-pr Magnetic Phase Diagrammentioning
confidence: 99%
“…Some such alloy systems that have been investigated earlier include Tb-Er, 21,22 Nd-Dy, 23 and Er-Pr. 24,25,26 In the Er-Pr system it was found that the addition of Pr significantly increases the heat capacity of Er, making the Er-Pr system suitable for cryocooler regenerator applications. 24,25 Multiple magnetic ordering transitions were recently discovered in pseudo-binary R 1-x R' x Al 2 alloys, where R and R' are rare earth metals with second order Steven's factors of opposite sign.…”
Section: Introductionmentioning
confidence: 99%